2004
DOI: 10.1103/physrevb.69.045403
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the force sensitivity of silicon cantilevers

Abstract: The resonance frequency and internal friction Q Ϫ1 of the first eigenmode of microfabricated silicon cantilevers are measured in the temperature range of 15-300 K. The analysis shows that variation of Young's modulus is responsible for the temperature dependence of the resonance frequency, whereas the dependence of the geometrical dimensions can be neglected. Accordingly, the data can be fitted by the Wachtman equation, yielding a Debye temperature ⌰ D ϭ634 K. The temperature variation of internal friction Q Ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 24 publications
6
97
0
3
Order By: Relevance
“…Advances in the study of thermoelastic damping 3.1. Experimental study of thermoelastic damping Gysin et al [27] measured the resonance frequency ω and internal friction damping was expected to vanish at 20K and 125K. A minimum of internal friction was observed at 20K, whereas the minimum at 125K appeared to be hidden by other dissipation effects.…”
Section: Zener's Theory Of Thermoelastic Dampingmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in the study of thermoelastic damping 3.1. Experimental study of thermoelastic damping Gysin et al [27] measured the resonance frequency ω and internal friction damping was expected to vanish at 20K and 125K. A minimum of internal friction was observed at 20K, whereas the minimum at 125K appeared to be hidden by other dissipation effects.…”
Section: Zener's Theory Of Thermoelastic Dampingmentioning
confidence: 99%
“…The intrinsic dissipation mechanism can be regarded as phonon-phonon interaction, namely the scattering of acoustic phonons with thermal phonons. [27] …”
Section: Description Of Thermoelastic Dampingmentioning
confidence: 99%
“…dominating cause of acoustic mode frequency drift [42,43]. The near-linear relation [41] ΔYT∕ΔT ≈ −7 MPa∕K allows the mode frequency to be used as a temperature probe.…”
Section: Predicted Performance Of a Practical Nsi Cavity Setupmentioning
confidence: 99%
“…The underlying sources of intrinsic cantilever dissipation remain under intense investigation both experimentally and theoretically. [185][186][187][188][189][190][191][192][193][194] Rast et al have shown that annealing single crystal silicon cantilevers in ultrahigh vacuum can improve their mechanical quality factors by an order of magnitude. 195 Nevertheless, achieving subattonewton sensitivity may require moving beyond single-crystal silicon oscillators.…”
Section: Future Directions In Mechanically Detected Magnetic Resmentioning
confidence: 99%